2017
DOI: 10.1371/journal.pone.0188089
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the metabolome in response to selection for increased immunity in populations of Drosophila melanogaster

Abstract: We used NMR-based metabolomics to test two hypotheses–(i) there will be evolved differences in the metabolome of selected and control populations even under un-infected conditions and (ii) post infection, the metabolomes of the selected and control populations will respond differently. We selected replicate populations of Drosophila melanogaster for increased survivorship (I) against a gram-negative pathogen. We subjected the selected (I) and their control populations (S) to three different treatments: (1) inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Previous reports have revealed that levels of intracellular leucine are increased due to dieldrin insecticide exposure in yeast , and another investigation on IMD-induced toxicity in freshwater snail has shown high levels of leucine . Hence, the change in leucine concentration could be a sign of increased immunity in response to injury or injection . With the above considerations/contemplations, leucine can be viewed as a marker for IMD exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have revealed that levels of intracellular leucine are increased due to dieldrin insecticide exposure in yeast , and another investigation on IMD-induced toxicity in freshwater snail has shown high levels of leucine . Hence, the change in leucine concentration could be a sign of increased immunity in response to injury or injection . With the above considerations/contemplations, leucine can be viewed as a marker for IMD exposure.…”
Section: Resultsmentioning
confidence: 99%
“…26 Hence, the change in leucine concentration could be a sign of increased immunity in response to injury or injection. 27 With the above considerations/contemplations, leucine can be viewed as a marker for IMD exposure. Serine, being a non-essential α-amino acid, aids in maintaining health and in disease prevention, and assumes an imperative part in cellular proliferation.…”
Section: Affected Metabolic Pathways In Drosophila Andmentioning
confidence: 99%